The Pre-Hippocratic medicine: - - Glišić, Miloš; Lazarević, Tatjana; Kovačević, Zoran; Janićijević Petrović, Katarina; Janićijević Petrović, Mirjana A.; Ljujić, Biljana (Vojnosanitetski pregled, 2022)
-
Keywords: egypt, ancient; greece, ancient; history, ancient; medicine, persian; medicine, traditional.